Profesor Roman Pollak jako współtwórca i JM Rektor Uniwersytetu Ziem Zachodnich - Franz, Maciej (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The aggression of Nazi Germany against Poland on September 1, 1939 was followed by the occupation of Poznan, during which the Germans dissolved the University of Poznań and wanted to denationalise Greater Poland by expelling Poles from the Warta Land, as they called it. Risking their lives, professors and students decided to create a secret University of the Western Lands in Warsaw and other cities of the General Government. It was the largest secret university in occupied Poland and one of its key figures was professor Roman Pollak. He was the second chancellor of the university, managing it during its greatestdevelopment.